A Pragmatic Analysis Of Directive Speech Acts In Alice In Wonderland Movie Script (2010) - KUSTANTINI, DEWI (2012)
This research concerns with directive speech acts in Alice in Wonderland Movie Script (2010). The goals of this research are to identify the language form, to describe the politeness pattern and to describe the implicature of directive speech acts in Alice in Wonderland Movie Script (2010). The researcher uses the descriptive qualitative as a type of the research. The data source of this research is the script of Alice in Wonderland (2010). The methods of collecting data are observation and documentation. The steps are watching, reading, selecting and collecting, and coding the data. The techniques of analyzing data are identifying the form by referring to language form, describing the politeness pattern based on the politeness theory in the field of pragmatic and describing the implicature based on pragmatic theory. This study shows the variety of the language form, the politeness pattern and the implicature of directive speech act in Alice in Wonderland Movie Script (2010). The variants of language forms are: Word (16,9%), Phrase (1,2%), Declarative sentence (16,9%), Interrogative sentence (4,8%), and Imperative sentence (60,2%). The politeness pattern: Bald on-record (77,1%), Positive politeness (2,4 %), negative politeness (3,6%), and off-record (16,9%). The imlicature: conventional implicature (83,1%), and conversational implicature (16,9%).